INVESTIGATION ON THE EFFECET OF POSTHAVEST PATHOGEN ON TOMATO QUALITY AND FARMERS IN SOME SELECTED LOCAL GOVERNMENT AREA OF ADAMAWA STATE, NIGERIA - Aji, M.B.; Hassan, Z.; Hasiya, U.J.; Njobdi, M.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the effect of Post-harvest pathogen on tomato quality and farmers livelihood in Adamawa State, Nigeria. Random Sampling Technique was used in selecting of 180 respondents from the study area. Data were collected through the administration of structured questionnaire and analyzed using both descriptive and inferential statistics. The results revealed that majority (72%52%) of the respondents were male and fell within the age bracket of 31-50 years. The results also showed that majority(61.3%) of respondents were aware of fungal pathogen infestation while (23.1% and 15.6%), were aware of bacterial and viral, respectively. The results further revealed that 38.9% and 33.3% of the respondents reported yield losses of more than 30 baskets due to pathogen infestation and use open baskets for transportation. Results show that while farmers widely recognize spoilage as a critical problem primarily caused by fungi they lack detailed knowledge of specific pathogens and modern storage practices. The study concluded that respondent’s demonstrated awareness of fungal tomato spoilage but remain largely uninformed about bacterial and viral threats. The study recommends the provision of affordable storage technology, investment in storage infrastructure, and evidence based policy interventions.